2001
DOI: 10.1097/00005537-200102000-00028
|View full text |Cite
|
Sign up to set email alerts
|

Submandibular Gland Transfer: A New Method of Preventing Radiation‐Induced Xerostomia

Abstract: We have successfully demonstrated that the submandibular gland can be surgically transferred to the submental space with its function preserved. The gland seems to continue functioning even after radiation therapy with the appropriate shielding. This surgical transfer procedure has the potential to change the way we currently manage patients with head and neck cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
79
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 16 publications
0
79
0
Order By: Relevance
“…The effective use of acupuncture is preferable to pharmacological agents (e.g., pilocarpine or amifostine) because acupuncture presents virtually no significant side-effects. In addition, patient dropout, which is common in studies using pharmacological agents, [6][7][8][9][10] was not seen in this study, showing the clinical feasibility of the therapy.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The effective use of acupuncture is preferable to pharmacological agents (e.g., pilocarpine or amifostine) because acupuncture presents virtually no significant side-effects. In addition, patient dropout, which is common in studies using pharmacological agents, [6][7][8][9][10] was not seen in this study, showing the clinical feasibility of the therapy.…”
Section: Discussionmentioning
confidence: 68%
“…6 Surgical submandibular salivary gland transfer to the submental space outside of the radiation field appears to be promising; however, there are specific restrictions on its indication and the technique is not available readily in oncology centers. 7 The cytoprotective agent amifostine combined with careful treatment planning, including intensity-modulated radiation therapy (IMRT), can minimize radiation-induced xerostomia; however, this drug is associated with unfavorable side effects and IMRT is not available in many oncology centers. [8][9][10] Despite the benefits of the above methods, all treatments have met with limited success.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that poor intraoral moistening lead to the onset of xerostomia, and they reported that when resting saliva secretion dropped to half of its baseline volume, patients experienced xerostomia. 9 Seikaly et al 21 and Al-Qahtani et al 22 reported that the preliminary surgical transplantation of submandibular glands contributed to the prevention of radiation-induced xerostomia. The fact that most resting saliva is supplied from the submandibular gland supports the relationship between submandibular gland hypofunction and xerostomia.…”
Section: Discussionmentioning
confidence: 99%
“…As early as 1911, Bergonie [57], a French radiobiologist, was the first to describe that radiotherapy destroyed the salivary function and caused eating difficulty. However, for 100 years, the discussions about postradiation xerostomia have never disappeared, although the definition and pathogenesis of postradiation xerostomia have already been accepted, and the prevention of postradiation xerostomia by transferring the submandibular gland into the submental space has become popular [10,25,31,32,37,38,43,44,45,46,47,48,49,50,51,52,53]. …”
Section: Discussionmentioning
confidence: 99%
“…In 2000, Jha et al [37] invented a new method of transferring the submandibular gland to the submental space with shielding in order to protect the gland function. Although submandibular gland transfer [38] has been widely accepted by patients and clinicians worldwide, there still is some controversy regarding its effectiveness and safety. So, the present systematic review and meta-analysis aimed to determine the effectiveness and safety of submandibular gland transfer for the prevention of postradiation xerostomia in head-and-neck cancer patients.…”
Section: Introductionmentioning
confidence: 99%